PROSES BERPIKIR KREATIF SISWA SMP DALAM PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI TIPE KEPRIBADIAN SISWA - Hidayatulloh, Hidayatulloh; Usodo, Budi; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2013)
Abstract: This research is aimed at describing the creative thinking process of students with rational personality type, idealist personality type, guardian personality type, andÂ  artisan personality type in solving mathematics problems. It was a descriptive qualitative research. The subject of this research was taken by using a purposive sampling. The subject of this research were 4 of the eighth grade students at SMP Negeri 2 Jenar, Sragen Regency, consisting of 1 student with rational personality type, 1 student with idealist personality type, 1 student with guardian personality type, and 1 student with artisan personality type. The techniques of collecting the data in this research were questionnaire, written test, and interview on plane geometri subject. The techniques of validating the data were time triangulation and sufficient references. The technique of analyzing the data was Miles and Huberman concept, namely, data reduction, data presentation, and conclusion drawing. The findings of the research show that (1) the student with rational personality type has creative thinking process level 1 (less creative); (2) the student with idealist personality type has creative thinking process level 3 (creative); (3) the student with guardian personality type has creative thinking process level 3 (creative); (4) the student with artisan personality type has creative thinking process level 0 (not creative). Keywords: Creative Thinking Process, Mathematics Problem Solving, Personality Type